2017
DOI: 10.1038/s41598-017-17172-w
|View full text |Cite
|
Sign up to set email alerts
|

Altered spontaneous calcium signaling of in situ chondrocytes in human osteoarthritic cartilage

Abstract: Intracellular calcium ([Ca2+]i) signaling is an essential universal secondary messenger in articular chondrocytes. However, little is known about its spatiotemporal features in the context of osteoarthritis (OA). Herein, by examining the cartilage samples collected from patients undergoing knee arthroscopic surgery, we investigated the spatiotemporal features of spontaneous [Ca2+]i signaling in in situ chondrocytes at different OA stages. Our data showed zonal dependent spontaneous [Ca2+]i signaling in healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 44 publications
4
12
0
Order By: Relevance
“…Because chondrocytes located in statically cultured cartilage explants are not compressed or exposed to osmotic tension, VDCCs might be the major candidate responsible for [Ca 2+ deposition (Fodor et al, 2013;Xu et al, 2009). This was supported by our previous study, in which we showed that chondrocytes in early degenerated human articular cartilage displayed stronger spontaneous [Ca 2+ ] i signaling, and correspondingly increased protein abundance of Ca v 3.3 (the α1 subunit of T-VDCC; Gong et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Because chondrocytes located in statically cultured cartilage explants are not compressed or exposed to osmotic tension, VDCCs might be the major candidate responsible for [Ca 2+ deposition (Fodor et al, 2013;Xu et al, 2009). This was supported by our previous study, in which we showed that chondrocytes in early degenerated human articular cartilage displayed stronger spontaneous [Ca 2+ ] i signaling, and correspondingly increased protein abundance of Ca v 3.3 (the α1 subunit of T-VDCC; Gong et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…Recent studies discovered that both isolated and in‐situ animal chondrocytes are able to display repetitive [Ca 2+ ] i signaling without any extracellular stimuli (O'Conor et al, ; Zhou, David et al, ). In addition, our recent study showed that in‐situ chondrocytes located in healthy human articular cartilage tissue were also capable to produce the zonal and OA severity dependent spontaneous [Ca 2+ ] i signaling (Gong et al, ). Given the fact that correlation between spontaneous [Ca 2+ ] i signaling and cartilaginous ECM maintenance has been demonstrated (Zhou, Park et al, ), spontaneous [Ca 2+ ] i signaling might be a key indicator of OA progression.…”
Section: Discussionmentioning
confidence: 99%
“…Articular cartilage and subchondral bone make an osteochondral unit in the joints [ 15 ]. Articular cartilage, including the superficial, middle, and deep layers [ 16 ], is responsible for biomechanical properties of a joint such as distribution of force, absorption of shock, and load-bearing that enables a pain-free and frictionless movement of the joint [ 17 , 18 , 19 ]. The superficial layer with a parallel structure of collagens and a high density of chondrocytes protects against shear and tensile stresses [ 16 , 20 ].…”
Section: Osteochondral Tissuementioning
confidence: 99%
“…It is assumed to involve in cell sensing substrate stiffness by locally altering the Ca 2+ permeability [28,29]. Since calcium signaling plays an important role in multiple signaling pathways and mechanotransduction in chondrocytes [30,31], substrate stiffness may modulate the chondrocyte mechanotransduction via the TRPV4-mediated Ca 2+ signaling, which eventually affects cell function [15]. Collectively, these ndings highlight the potential role of substrate stiffness in regulating the RVD response and TRPV4-mediated calcium signaling in chondrocytes.…”
Section: Introductionmentioning
confidence: 99%